Technology, energy, and time – Experimental paths for the design of appropriate technology - Annapaola Vacanti; Carmelo Leonardi (Agathón)
Exploring the intertwining of technology, energy, and time from the Industrial Revolution to the current climate crisis, the paper investigates how the relentless pursuit of efficiency and productivity has shaped Western societies, increasing energy overconsumption and exacerbating environmental emergencies. Analysing experimental paths related to the concept of appropriate technology, such as Permaculture, Low-tech and Solarpunk, a critical view of the contemporary unsustainable development model is presented, proposing alternative paradigms that foster sustainability, equity and reconnection with natural cycles. The multidisciplinary design approach emerges as instrumental in the transition to sustainable energy practices, laying the foundation for the transition to future scenarios in which technology and nature coexist harmoniously.